(untitled) (Tanzania Medical Journal, 2007)
The objectives of this study were to determine the vertical transmission rate of hepatitis B virus (HBV) infection and the socio-demographic factors associated with its transmission in pregnant women (PW). The subjects were pregnant women who presented for delivery in the prenatal wards and their newborns at Muhimbili Medical Centre, Mwananyamala, Ilala and Temeke Hospitals in Dar es Salaam between April and December 1995. Women who consented to participate in the study were interviewed according to a questionnaire established for this purpose. Sera were taken from all study subjects and subjected to testing for hepatitis B surface antigen (HBsAg). Babies who were HBsAg negative at birth but born of HBsAg positive mothers were re-tested at the ages of 3 and 6 months. Of the 1540 PW studied, 54 (3.5%) were HBsAg positive and they gave birth to 54 infants. Of the 54 infants, three (5.5%) were excluded from the study for various reasons. Two of the 51 infants (3.9%) were HBsAg positive at birth and four (7.9%) at three months. Hence, the vertical transmission rate was 11.8%. Frequent injections in the past were found to be significantly associated with increased risk for HBV infection in the mothers (Fisher's exact test: p = 0.001). We conclude that the vertical transmission rate is high (11.8%) and that the transmission occurs before birth and within 3 months after delivery. It is recommended that apart from introducing vaccination for under-fives, the vaccination should also be extended to PW as part of routine antenatal care. Keywords: Hepatitis B virus infection, vertical transmission, pregnant women, Tanzania Tanzania Medical Journal Vol. 19 (1) 2004: pp.